Politically connected boards, family and business group affiliations, and cost of capital: Evidence from Indonesia. Issue 3 (May 2020) - Joni, Joni; Ahmed, Kamran; Hamilton, Jane
Abstract: We investigate the effect of politically connected boards (both supervisory boards [SBs] and boards of directors [BODs]) on cost of debt and equity capital of listed companies in Indonesia which has established a two-tier corporate governance system. The results, based on 250 firms, suggest that companies with politically connected SBs experience lower cost of debt and equity capital, whereas politically connected BODs have no association with cost of either debt or equity. Furthermore, we find that family firms and firms belonging to business groups with politically connected SBs enjoy lower cost of debt and equity capital. Our main results are robust to alternative measures and to tests for endogeneity. Highlights: We investigate the effect of politically connected SBs and BODs on cost of capital in Indonesia. The results show that firms with connected SBs pay lower cost of capital, whereas connected BODs have no association. We also find that family firms and business groups with politically connected SBs enjoy lower cost of debt and equity.